Effect of welding repair on mechanical properties of ASTM A36 carbon steel weld joints - Azwinur, Azwinur; Syukran, Syukran; Akhyar, Akhyar; Tho, Nguyen Huu; Jaswir, Jaswir (Jurnal Polimesin, 2022)
The welding repair process greatly affects the procedure of a welding process to be able to obtain the results of a connection that is safe and in accordance with its provisions. The strength of the welded joint must be considered and ensured that its strength is at least close to the original strength of the material used. In a welding process, errors or omissions are often made accidentally by the welder or the work environment and the selection of welding variable parameters is not appropriate so that welding defects occur. Welding defects can affect the strength of the weld joint. The purpose of this study was to determine the effect of welding repair on the mechanical properties of ASTM A36 material. The material used in conducting this research and testing is ASTM A36 steel plate. Welding was carried out on 4 specimens with the method without repair, repair 1x, repair 2x and repair 3x. Based on the test results, the number of repairs greatly affects the strength of the material connection. The highest maximum tensile strength value in 1 repair specimen is 501.90 Mpa and the lowest is in unwelded material or base metal of 467.97 Mpa. The results of the highest hardness test on the repair material 1 time of 30.83 HRC in the weld metal area and the lowest hardness value on the repair specimen 3 times in the HAZ area of 21 HRC. The results of the macro photo test on each specimen did not detect any welding defects on the inside of the welded material. the largest HAZ width in the 3 times repair material is 21.5 mm and the smallest HAZ width in the specimen without repair is 18 mm